La obra literaria de Emilio Carrere (IV): Emilio Carrere y sus tres últimos poemarios - Labrador Ben, Julia María; Sánchez Álvarez-insúa, ALBERTO (Dicenda. Estudios de lengua y literatura españolas, 2005)
This current work concludes the exhaustive review of the poetic task of Emilio Carrere Moreno (Madrid, 1881-1947). His poetic and literary biography is completed in this forth issue, and his ninth, tenth and eleventh poem collections are also studied within: Panderetas de España, Poesías (La canción de la calle y otros poemas) and Ruta emocional de Madrid. There is a description of publications, its critical reception is announced and the contents and metrics of his poems are analized. An index of his first verses is included.